2016
DOI: 10.1177/1557988315624509
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Perceived Discrimination on Depressive Symptoms Among Black Men Residing in the United States: A Meta-Analysis

Abstract: Research reports that perceived discrimination is positively associated with depressive symptoms. The literature is limited when examining this relationship among Black men. This meta-analysis systematically examines the current literature and investigates the relationship of perceived discrimination on depressive symptoms among Black men residing in the United States. Using a random-effects model, study findings indicate a positive association between perceived discrimination and depressive symptoms among Bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 73 publications
4
51
1
Order By: Relevance
“…Across diverse ethnic populations, positive associations were found between ethnic discrimination and emotional distress, as well as inverse associations with positive markers of well‐being, such as self‐esteem and self‐efficacy . Several recent reviews continue to document an inverse association between discrimination and good mental health . For example, a 2014 review reported the results of two meta‐analyses focused on the association between discrimination and well‐being .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Across diverse ethnic populations, positive associations were found between ethnic discrimination and emotional distress, as well as inverse associations with positive markers of well‐being, such as self‐esteem and self‐efficacy . Several recent reviews continue to document an inverse association between discrimination and good mental health . For example, a 2014 review reported the results of two meta‐analyses focused on the association between discrimination and well‐being .…”
Section: Resultsmentioning
confidence: 99%
“…20 Several recent reviews continue to document an inverse association between discrimination and good mental health. [21][22][23][24][25][26][27] For example, a 2014 review reported the results of two meta-analyses focused on the association between discrimination and well-being. 28 Discrimination, in the first meta-analysis, was associated with poorer well-being (self-esteem, depressive and anxiety symptoms, psychological distress, and life satisfaction), with the association being somewhat weaker for positive outcomes than negative ones.…”
Section: Discrimination and Mental Healthmentioning
confidence: 99%
“…Psychology researchers have sought to define racial discrimination, explore its harmful impacts on victims, and determine potential coping mechanisms to mitigate these adverse effects. Results show that perceived racial discrimination is negatively associated with psychological (Britt-Spells, Slebodnik, Sands, & Rollock, 2018;Lee & Ahn, 2011;Pieterse et al, 2012) and academic outcomes (Alliman-Brissett & Turner, 2010;Benner et al, 2018). This chapter will review the current racial discrimination literature, illuminate gaps, and propose a study to investigate the potential moderating effects of ethnic-racial socialization on the relationship between perceived discrimination and several psychological and academic outcomes among African American young adults.…”
Section: Chapter 2 Literature Reviewmentioning
confidence: 99%
“…Despite the extensive research on racial discrimination, there is no one agreed-upon definition for the construct. Some scholars define racial discrimination as wrongful acts or unfair treatment toward an individual or group based on racial or ethnic identity (Britt-Spells et al, 2018;Jones & Carter, 1996), suggesting that racial discrimination is behavioral. In contrast, others describe racial discrimination as a combination of unfair treatments, beliefs, values, and ideologies regarding the inferiority of racial or ethnic minorities (Belgrave & Allison, 2014;Clark, Anderson, Clark, & Williams, 1999).…”
Section: Defining Perceived Racial Discriminationmentioning
confidence: 99%
“…One of the main environmental factors recognized to be able to potentially precipitate depressive symptoms is stress. Stressful events (divorce, death of a relative, childhood maltreatment, unemployment, poverty, racial discrimination etc) increase the risk of MDD manifestation in susceptible individuals (Vinkers et al, 2014;McLaughlin et al, 2010;Britt-Spells et al, 2018).…”
Section: Introductionmentioning
confidence: 99%